2020
DOI: 10.21203/rs.3.rs-27046/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why do pregnant women prefer cesarean birth? : a qualitative study in a tertiary care center in Southern Thailand

Abstract: Background: The increasing worldwide rate of cesarean sections is of global concern. In recent years, cesarean births upon maternal request have become both a hotly debated issue. Hence, this study aimed to explore maternal reasons for cesarean preference without medical indications.Methods: A descriptive qualitative study was conducted, using in-depth interviews with 27 pregnant women, attending antenatal care in Songklanagarind Hospital from September 2018 to June 2019, who preferred cesarean birth. Data wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…Studies have reported the likelihood of CS delivery to increase with higher wealth quintiles, in congruity with the findings of this study [17,20,25,26]. Most women now do not want to go through vaginal delivery since it is perceived as painful; hence, they opt for CS to avoid the pain [27].…”
Section: Discussionsupporting
confidence: 84%
“…Studies have reported the likelihood of CS delivery to increase with higher wealth quintiles, in congruity with the findings of this study [17,20,25,26]. Most women now do not want to go through vaginal delivery since it is perceived as painful; hence, they opt for CS to avoid the pain [27].…”
Section: Discussionsupporting
confidence: 84%